Evaluating the PCPT risk calculator in ten international biopsy cohorts: results from the Prostate Biopsy Collaborative Group. - Ankerst, D; Boeck, A; Freedland, S; Thompson, I; Cronin, A; Roobol, M; Hugosson, J; Stephen Jones, J; Kattan, M; Klein, E; Hamdy, F; Neal, D; et al. (2012)
OBJECTIVES: To evaluate the discrimination, calibration, and net benefit performance of the Prostate Cancer Prevention Trial Risk Calculator (PCPTRC) across five European randomized study of screening for prostate cancer (ERSPC), 1 United Kingdom, 1 Austrian, and 3 US biopsy cohorts. METHODS: PCPTRC risks were calculated for 25,733 biopsies using prostate-specific antigen (PSA), digital rectal examination, family history, history of prior biopsy, and imputation for missing covariates. Predictions were evaluated using the areas underneath the receiver operating characteristic curves (AUC), discrimination slopes, chi-square tests of goodness of fit, and net benefit decision curves. RESULTS: AUCs of the PCPTRC ranged from a low of 56% in the ERSPC Goeteborg Rounds 2-6 cohort to a high of 72% in the ERSPC Goeteborg Round 1 cohort and were statistically significantly higher than that of PSA in 6 out of the 10 cohorts. The PCPTRC was well calibrated in the SABOR, Tyrol, and Durham cohorts. There was limited to no net benefit to using the PCPTRC for biopsy referral compared to biopsying all or no men in all five ERSPC cohorts and benefit within a limited range of risk thresholds in all other cohorts. CONCLUSIONS: External validation of the PCPTRC across ten cohorts revealed varying degree of success highly dependent on the cohort, most likely due to different criteria for and work-up before biopsy. Future validation studies of new calculators for prostate cancer should acknowledge the potential impact of the specific cohort studied when reporting successful versus failed validation.